An electrochemical impedance spectroscopy study of Al-Zn and Al-Zn-Sn Alloys in tropical seawater - M. C., Isa; Abdul Razak, Daud; M. Y., Ahmad; M., Daud; Shaiful Rizam, Shamsudin; N., Hassanuddin; M. S., Din Yati; M. M., Muhammad (Trans Tech Publications, Switzerland, 2012)
Link to publisher's homepage at http://www.ttp.net/